Development of Physical Fitness Evaluation Criteria for Women in Compulsory Isolation for Drug Rehabilitationn in Compulsory Isolation for Drug Rehabilitation - Yang, Yi; Luo, Jiong (Quality in Sport, 2024)
Background: The issue of physical and mental rehabilitation for drug users lacks a comprehensive and reliable system for evaluating it difficult to conduct a reasonable assessment of their physical fitness.The establishment of physical fitness evaluation criteria specifically tailored for female drug users serves as the fundamental basis for developing precise and individualized exercise prescriptions.Methods:This study used the national physical fitness test method to assess the physical fitness of female drug addicts undergoing mandatory rehabilitation. The principal component analysis method was employed to calculate the weight of each individual physical fitness test indicator, which was then combined with the indicator T score to obtain a comprehensive evaluation of the physical fitness of these individuals.On this basis, a single physical fitness index T-score scoring equation was determined for two groups of women (with and without diseases) undergoing compulsory isolation and drug rehabilitation, stratified by age (under 30 years old, 31-40 years old, 41-50 years old, 51-60 years old).Results: The weights of various indicators and the combined weights of secondary indicators in the physical fitness evaluation index system for female addicts undergoing compulsory isolation for detoxification have been established. Conclusion:Based on the total score calculated by combining the T-score of each individual physical fitness indicator with its corresponding weight, a comprehensive rating system with four levels - "excellent, good, qualified, and unqualified" - has been set.